ANALISIS VEGETASI DAN PENDUGAAN KARBON TERSIMPAN PADA POHON DI KAWASAN SEKITAR GUNUNG DAN DANAU BATUR KINTAMANI BALI - Sujarwo, Wawan; Darma, I Dewa Putu (Bumi Lestari, 2011)
Reforestation program of bare land with planting several species of trees has been done on several areas around Mountain and Lake Batur. So that, the study of trees vegetation analysis and estimating of carbon stock needs to be done as well. A total 2400 m2 Sampling Plot with 6 plots (20 x 20 m) in four areas has been established to determine trees structure, composition, and carbon stock (above ground) in around Mountain and Lake Batur Kintamani. Enumeration of all tree species revealed that there were 11 species and 10 families with Eucalyptus urophylla (Myrtaceae) was the most abundant species and family in the Sampling Plot with INP was 97.24%. Shannon Index (H’) revealed that tree species composition was 0,8. It means the diversity of trees is low. The amount of carbon stock (above ground) was 28.0669 ton per 0.24 Ha. It means, total carbon stock in 400 Ha secondary forest around Mountain and Lake Batur was 46,778.17 ton.
Keywords: vegetation analysis; carbon stock; trees; Kintamani